The Use of NHT and TPS Assisted by Zoom Meetings on the Problem Solving Ability of Elementary School Students - Handayani, Sri Lestari; Muamar Isyanto; Khairil Ibrahim; Kusmajid (Universitas Pendidikan Ganesha, 2022)
Learning science in elementary schools still carried out conventionally which results in the lack of problem solving abilities in students. NHT and TPS are a kinds of methods that can support students’ problem solving abilities. This study was conducted to analysis the differences in students' science problem-solving abilities between the application of NHT and TPS learning materials for class IV public schools. This research was conducted in the form of experimental research using Quasy Experimental Design. The design used is Non Equivalent Control Group Posttest Design. The population in this study were 58 students in class IV. Sampling was carried out using a saturated sample technique in class IV A with a total of 28 students as experimental class I (NHT) and Class IV B with a total of 30 students being treated with TPS. The data collection technique used a test in the form of a posttest. These results indicate that there are dissimilarities or differences between the problem-solving abilities of fourth-grade students in experimental class I (NHT) and practical class II (TPS), especially in sound material. The NHT model that is applied has more influence on students' problem-solving abilities in the teaching and learning process compared to the TPS model.